THE GREATER OMENTUM AS A PERIPHERAL ORGAN OF THE IMMUNE SYSTEM: MORPHOLOGICAL AND FUNCTIONAL ASPECTS - Fedorchenko, Igor; Maksymenko, Oleksandr; Hryn, Volodymyr; Bilash, Valentyna; Tykhonova, Olesia; Tarasenko, Yana (Eastern Ukrainian Medical Journal, 2025)
Introduction. The greater omentum, despite its apparent simplicity at first glance, is a complex anatomical structure with multiple functions. Active involvement of the greater omentum in the protection of the abdominal cavity, along with its unique plastic properties, makes it an important subject of study for surgeons and researchers. Moreover, the presence of specialized lymphoid structures in the greater omentum highlights its significant role in the body’s immune system. Methods. The analytical review was conducted based on published articles, books, educational manuals and monographs. The literature search was performed on the global Internet using scientific databases such as Google Scholar, Web of Science and PubMed, as well as the electronic library of Poltava State Medical University. Results and Discussion. The greater omentum is not merely a fatty fold in the abdominal cavity but a complex organ with numerous functions. Although it has been known to humanity since the ancient times, its detailed study has begun recently. This organ consists of several layers of peritoneum and contains a significant amount of adipose tissue, blood vessels, nerves and lymphoid structures known as “milky spots.” It is the milky spots that endow the greater omentum with immune properties, helping the body combat infections. In addition to its immune function, the greater omentum performs several other critical roles: it protects internal organs from damage, participates in metabolic processes and can even be used in surgery for tissue reconstruction. The shape and size of the greater omentum can vary among individuals, depending on the unique characteristics of their bodies. With age, the structure and functions of this organ also undergo changes. Despite numerous studies, the greater omentum still holds many mysteries. Further research into this organ will allow for a deeper understanding of the processes occurring in the human body and the development of new methods for treating various diseases. Conclusions. The analysis of the presented data provides a detailed understanding of the greater omentum as a dynamic organ that plays a key role in the functioning of the abdominal cavity. Derived from the peritoneum, it is not merely a passive element but an active participant in numerous physiological processes. The mobility of the greater omentum, facilitated by its structure, allows it to function as a protective “apron,” shielding internal organs from damage and infection. Additionally, its proximity to many organs of the digestive system contributes to maintaining homeostasis within the abdominal cavity. The presence of milky spots gives the greater omentum immunological properties. These structures act as specialized “outposts” of the immune system, continuously monitoring the antigenic composition of the abdominal cavity. Their location within the greater omentum underscores the importance of this organ in providing local immunity.